Begonia colliculata (Begoniaceae), a new species from Nam Kading National Protected Area, Bolikhamxai province, Laos - Souvannakhoummane, Keooudone; Lanorsavanh, Soulivanh; Park, Jeong Ho; Kang, Ho Sang; Ahn, Tai Hyeon; Xayalath, Singkone; Phongoudom, Chanhsamone (Thai Forest Bulletin (Botany), 2020)
Begonia colliculata is described and illustrated with photographs from Nam Kading National Protected Area, in the Bolikhamxai Province of Laos.